Benefits of the Implementation of Gamification on Virtual Learning Environments - Carpio Beltrán, Íngrid Soraya
In recent years, the implementation of technological tools has taken a fundamental role in virtual learning environments. Educators have begun to innovate their classes through the application of these new technologies, which present an enormous variety of advantages that help to facilitate the teaching-learning process in virtual environments. The purpose of this academic paper is to describe the activities developed during the Specialization Course in the Administration of Virtual Environments for Foreign Languages Teaching and Learning offered by the Language Department of the University of El Salvador. The course was divided in three modules, and each one of them provided significant learning about theories of learning in virtual environments, learning management systems (LMS), platforms for video conferences, technological tools, fundamentals and principles of using technological tools, fundamentals of using multimedia resources in a virtual learning Environment, and the creation and appropriate use of didactics materials. In addition, the report presents an overview of online education, virtual learning environments and gamification, which are important topics studied during the specialization course.